Calidad de servicio percibida por los usuarios del área de consulta externa del Hospital Provincial General de Latacunga. - Lasinquiza Laica, Jenny Elizabeth (2020)
The Quality of Service currently takes an important role in public and private organizations, guaranteeing the full satisfaction of users, both internal and external, to meet their expectations and needs. The present investigation consists in the Quality of the Service, with the Main Objective: To evaluate the level of satisfaction of the quality of the service perceived by the users of the external consultation Area of the General Provincial Hospital of Latacunga. The descriptive methodology was used and as a tool the SERVQUAL measurement instrument of the authors (Zeithaml, Parasuraman and Berry, 2014), was applied considering (22) items of expectations and (22) items of preceptions with a Likert scale from 1 to 7. The Instrument assessed five dimensions: Reliability, Responsiveness, Security, Empathy and Tangible Aspects. The questionnaire was applied the 365 users from the External Consultation Area from the General Provincial Hospital of Latacunga. From the analysis of the data performed, it was identified that in the five dimensions of the SERVQUAL survey, users perceive the Satisfaction Level as Acceptable, reaching a percentage of 70.94%, demonstrating that the Quality of Service, they receive is high and meet their needs.